Parallel computing technologies 11th International Conference, PaCT 2011, Kazan, Russia, September 19-23, 2011. Proceedings - Malyshkin, Victor; SpringerLink (Online service). (Heidelberg Springer, 2011)
This book constitutes the proceedings of the 11th International Conference on Parallel Computing Technologies, PaCT 2011, held in Kazan, Russia on September 19-23, 2011. The 44 full papers presented together with 2 invited papers were carefully reviewed and selected from 68 submissions. The papers are organized in topical sections on models and languages, cellular automata, parallel programming tools and support, and applications.
Electronic reproduction.
Keywords: Parallel processing (Electronic computers) -- Congresses; Electronic books